MENGKRITISI TRADISI BERBAGI DALAM UPACARA ADAT NGGUA LIO-ENDE FLORES NTT DALAM TERANG TEOLOGI PEMBEBASAN GEREJA KATOLIK - Mathias Jebaru Adon; Kristoforus Garnodin; Siklus Depa (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
The focus of the discussion in this study lies in the critical dimension of the 'sharing' tradition in the Nggua traditional ceremony of the Lio-Ende Flores tribe. The tradition of 'sharing' in the traditional Nggua ceremony is a form of gratitude as well as an opportunity to help each other. Reality shows that this tradition has created poverty for the Lio-Ende tribal community because the local community is forced to carry out the Nggua ceremony even though they are economically unable. Therefore, this study aims to provide a philosophical understanding to the Lio-Ende community about the meaning of the Nggua ceremony as a harvest thanksgiving ceremony in the light of the liberation theology of the Catholic Church. This effort is expected to have a significant impact on changing the perspective of the local community in understanding Nggua traditional ceremonies. The research methodology was used in the form of qualitative data collection through interviews. Interviews were conducted by telephone or video call. This study finds that the Lio-Ende community is trapped in a wrong perspective on the meaning and message of the Nggua adat. This way of thinking has made their lives trapped in poverty because of the wrong meaning of culture. This happens because of the shallow meaning of the message conveyed in the Nggua traditional ceremony. In this situation, the Church is present as the party proclaiming liberation so that they can interpret the Nggua ceremony as a celebration of thanksgiving for the harvest.